The Study of Value-Semantic Orientation Problem in the Context of Professional and Personal Self-Development of Future Teachers - Zhilgildinova, Madina; Dyusembaevich Kariyev, Adlet; Toktacinovna Selkebayeva, Aiman; Alikhankyzy, Guliya; Turganbayeva, Beibitgul (International Journal of Engineering and Technology, 2018)
The article presents the empirical research results aimed at determining the level of mastering the abilities to professional and personal self-development of pedagogical specialty students. Based on the analysis of psychological and pedagogical literature, the concept of "self-development of future teachers" was defined and formulated. The study offers a detailed prognostic model of stimulation of professional and personal self-development of future teachers. Based on system analysis, the authors have defined and presented the structure of stimulation of professional and personal self-development of future teachers. In the proposed structure of stimulation, the authors distinguished motivational, cognitive, and value-semantic components. The study comprehensively examines the value-semantic component as one of the main factors stimulating the professional and personal self-development of pedagogical specialty students. The results of empirical research on stimulation of professional and personal self- development of future teachers are presented using diagnostic methodologies. Â